Outer retina micro-inflammation is driven by T cell responses prior to retinal degeneration in early age-related macular degeneration - Stürzbecher, Lucas; Bartolomaeus, Hendrik; Bartolomaeus, Theda U. P.; Bolz, Sylvia; Sekulic, Andjela; Ueffing, Marius; Clark, Simon J.; Reichhart, Nadine; Crespo-Garcia, Sergio; Wilck, Nicola; Strauß, Olaf (Frontiers in Immunology, 2025)
IntroductionAge-related macular degeneration (AMD) is a leading cause of blindness with limited treatment options. Dysfunction of the retinal pigment epithelium (RPE) is a unifying salient feature of the pathology and a primary end-point damage leading to complications such as geographic atrophy (GA), which represents the most common end-stage of AMD.MethodsHuman and murine ocular tissues were used for histological examinations. Furthermore, flow cytometry and gene expression analysis were used on ocular and splenic tissues of Cx3cr1GFP/GFP and C57BL/6J mice at 8 and 12 months of age to characterize the dynamics of local and systemic T cell populations.ResultsWe show the presence of memory T cells such as CD45RO+ cells in the choroid and retina of patients with AMD with a peak of abundance in early stages of AMD. As further evidence for the contribution of the adaptive immune system to GA we identified an increased frequency of CD44+ CD69+ KLRG1+ T cells and para-inflammation of the retina in a mouse model that mimics features of GA. Importantly, the activation of T cells found at early AMD-like stages prior to degeneration possessed long-lasting cytotoxic properties and adopted typical features of senescent immune cells. T cells were intimately associated with the RPE, suggesting transmigration and participating in local micro-inflammation.DiscussionOur data support that activation and accumulation of memory T cells can be considered as a hallmark of early AMD, and that adaptive immunosenescence likely to contribute to the chronic inflammation associated with RPE damage and the progression to large lesions as seen in GA.